The Sociology of formal organizations - Chaturvedi, Abha.; Chaturvedi, Anil, 1948- (Bombay ; New York : Oxford University Press, 1995)
Contributed research papers; with reference to India.
Includes bibliographical references (p. [357]-382) and index.
Keywords: Organizational sociology; Organizational behavior -- India